CRISM‐Based High Spatial Resolution Thermal Inertia Mapping Along Curiosity's Traverses in Gale Crater. Issue 5 (23rd May 2022) - Christian, John R.; Arvidson, Raymond E.; O'Sullivan, Joseph A.; Vasavada, Ashwin R.; Weitz, Catherine M.
Abstract: Thermal inertia is a key summary property describing the thermophysical characteristics of geologic materials. Orbital estimates of thermal inertia are especially useful in conjunction with rover‐based observations to provide additional constraints on material properties and to interpret the broader region surrounding the traverse. We have developed an approach to estimate apparent thermal inertias (ATI) from observations from the Mars Reconnaissance Orbiter's Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) at a much higher spatial resolution than is available from any other orbital data set. We apply this method to along‐track oversampled scene FRT00021C92 over Gale Crater within Glen Torridon, where the Curiosity rover has traversed; the retrieved values are then analyzed along with remote sensing and in‐situ observations by Curiosity to characterize surface properties in and around Glen Torridon. CRISM‐based ATI estimates of basaltic sand fields indicate a correlation between higher ATI values and the abundance of large (up to 3 mm in size) grains on the crests and flanks of large ripples. On the Vera Rubin ridge, ATI estimates are used to identify a west‐to‐east increase in the abundance of rock fragments within unconsolidated surface cover. On the Greenheugh pediment, an unmixing approach is used to identify a thin layer of wind‐blown sand sourced from the nearby Sands of Forvie. Finally, within Glen Torridon, a north‐to‐south increase in the mean and width of the ATI distribution is identified as a consequence of increased bench‐like bedrock exposures. Plain Language Summary: We used images taken by an instrument on the Mars Reconnaissance Orbiter to estimate a property called thermal inertia in the area surrounding the Curiosity rover, which can be used to distinguish solid rock from sand or other loose material. By correlating our orbital estimates with observations from Curiosity, we were able to constrain a variety of surface properties at various locations along Curiosity's traverse. In sand fields, we were able to determine whether large sand grains (up to a few mm in size) are present on ripple crests, which provides constraints on ripple activity. On the Vera Rubin ridge, we identified an increase in the amount of rock fragments when moving from west to east along the ridge. On the Greenheugh pediment, these estimates along with spectral data identified a thin layer of sand cover blown in from the nearby Sands of Forvie. Finally, within Glen Torridon, changes in thermal inertia have been identified that correspond to the presence of periodic bedrock ridge structures, which may help to constrain models of their formation. Key Points: Orbital thermal inertia is estimated from Compact Reconnaissance Imaging Spectrometer for Mars data at a resolution of 12 m/pixel Unmixing models are applied to identify spatial changes in bedrock and regolith properties in Gale Crater